Treatment of childhood acute lymphoblastic leukemia in central America: A lower‐middle income countries experience. Issue 5 (24th December 2013) - Navarrete, M.; Rossi, E.; Brivio, E.; Carrillo, J.M.; Bonilla, M.; Vasquez, R.; Peña, A.; Fu, L.; Martinez, R.; Espinoza, C.M. Pacheco; Lacayo, L.F. Baez; Rodriguez, H.; et al.
<x xml:space="preserve">Abstract</x> Background Five Asociación de Hemato‐Oncología de Centroamérica (AHOPCA) countries have used an adapted BFM‐based protocol for childhood acute lymphoblastic leukemia (ALL). Procedure In the AHOPCA‐ALL 2008 protocol, patients were stratified by age, white blood cell count, immunophenotype, central nervous system involvement, day 8 prednisone response, and morphologic bone marrow response to induction therapy. Patients at Standard Risk (SR) received a three‐drug induction regimen, a reinduction phase, and maintenance with protracted intrathecal therapy. Those at Intermediate (IR) and High Risk (HR) received, in addition, daunorubicin during induction therapy, a consolidation phase and two or three reinduction phases respectively. Results From August 2008 through July 2012, 1, 313 patients were enrolled: 353 in SR, 548 in IR, 412 in HR. During induction therapy, 3.0% of patients died, 2.7% abandoned treatment, 1.1% had resistant ALL, and 93.2% achieved morphological complete remission (CR). Deaths and abandonment in first CR occurred in 2.7% and in 7.0% of patients, respectively. The relapse rate at a median observation time of 2.1 years was 15.0%. At 3 years, the event‐free survival (EFS) and overall survival (OS), with abandonment considered as an event, were 59.4% (SE 1.7) and 68.2% (SE 1.6). Three‐year EFS was 68.5% (SE 3.0), 62.1% (SE 2.6), and 47.8% (SE 3.2) for SR, IR, and HR groups. Adolescents had a significantly higher relapse rate (P = 0.001). Conclusions This experience shows that common international studies are feasible in lower‐middle income countries. Toxic deaths, abandonment of treatment, and relapses remain major obstacles to the successful treatment. Alternative treatment strategies may be beneficial. Pediatr Blood Cancer 2014;61:803–809. © 2013 Wiley Periodicals, Inc.